2014
DOI: 10.3892/or.2014.2986
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Aurora kinase A by RNA interference inhibits tumor growth in human osteosarcoma cells by inducing apoptosis and G2/M cell cycle arrest

Abstract: The overexpression of Aurora kinase A (AURKA), a member of serine/threonine kinase family, has been observed in various types of human cancers. However, the role of AURKA in osteosarcoma (OS), the most common type of primary malignancy arising from bone, has not been clarified. We used AURKA-specific lentivirus-delivered short hairpin RNA (shRNA) to significantly and sustainably silence the endogenous AURKA expression in human OS cells SAOS-2 and U2OS. We found that AURKA downregulation in OS cells prominently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…CENPA phosphorylation requires the enrichment of AURKB to maintain the phosphorylation on Ser7 at inner centromeres and for kinetochore function [ 26 28 ]. Jiang et al [ 29 ] showed that silencing of AURKA expression in osteosarcoma cells significantly decreased both colony formation ability in vitro and tumorigenesis ability in vivo as well as induced cell apoptosis and G2/M cell cycle arrest in osteosarcoma cells. In addition, the median survival time was significantly longer in patients with low- CENPA expression osteosarcomas than in those with high- CENPA expression osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…CENPA phosphorylation requires the enrichment of AURKB to maintain the phosphorylation on Ser7 at inner centromeres and for kinetochore function [ 26 28 ]. Jiang et al [ 29 ] showed that silencing of AURKA expression in osteosarcoma cells significantly decreased both colony formation ability in vitro and tumorigenesis ability in vivo as well as induced cell apoptosis and G2/M cell cycle arrest in osteosarcoma cells. In addition, the median survival time was significantly longer in patients with low- CENPA expression osteosarcomas than in those with high- CENPA expression osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora kinase A and B are overexpressed in various sarcomas, including chondrosarcoma, osteosarcoma, synovial sarcoma, and Ewing sarcoma, and are associated with poor prognosis and metastasis 104107 . Targeting aurora kinase A and B with small molecule kinase inhibitors, shRNA, and siRNA exhibited inhibition of tumor cells 105, 107 . Moreover, a study demonstrated that the combination of aurora kinase A and B kinase inhibitor VX-680 (Tozasertib) with etoposide and doxorubicin showed synergistic effects in Ewing sarcoma 107 .…”
Section: Targeting Serine/threonine Protein Kinases To Reverse Mdr Inmentioning
confidence: 99%
“…The solution may thus not lie in targeting DNA, but rather in identifying other relevant cellular targets in osteosarcoma cells. Current investigation in the field suggests the Wnt signalling pathway (Guo et al 2007), the aurora kinase A (AURKA) (Jiang et al 2014), and the Rhoassociated coil containing protein kinase 1 (ROCK1) (Liu et al 2011) as promising new targets for the inhibition of osteosarcoma growth and/or progression.…”
Section: Discussionmentioning
confidence: 99%